Information technology literacy among form four and five students in Maktab Rendah Sains MARA (MRSM) Merbok, Kedah / Muhammad Hazim Shuhaili - Shuhaili, Muhammad Hazim (2012)
The research was undertaken to examine the information technology literacy among form four and five students in Maktab Rendah Sains MARA (MRSM) Merbok, Kedah. The focus of this study the level of information literacy of form 4 and 5 students. The instrument for the study was a set of questionnaires. That was distributed to 164 students in form 4 and 5 students from Maktab Rendah Sains MARA (MRSM) Merbok. Type of investigation that be used in this research is correlation whereby it will look at the relationship between all variables. There a one dependent variable and three independent variable for this research. The dependent variable is the literacy among form 4 and 5 students and the independent variables are usage, evaluation and access of information technology in the school. The scope of this research is only among Maktab Rendah Sains MARA (MRSM) Merbok student that are in form 4 and form 5. There are four limitations that need to be during conducted this research which are time constrains, lack of school cooperation, study the level of information literacy of form 4 and 5 students, lack of Time, and lack of experience in conducting this research.